Pneumonia Corona Virus Infection Disease-19 (COVID-19) - Isbaniah, Fathiyah; Susanto, Agus Dwi (Majalah Kedokteran Indonesia, 2020)
Since the beginning of 2020 there has been an increase in the number COVID-19 virus infection, previously known as 2019-nCov. It is known that up to February 2020, more than 70,000 positive cases of COVID-19 infection have been confirmed. COVID-19 is known to be a virus from the coronaviridae family, which is also a family of the SARS-CoV and MERS-CoV viruses that caused an outbreak in 2002 and 2012. The exact pathogenesis of COVID-19 is not clearly known, but is thought to be similar to the pathogenesis of SARS-CoV and MERS-CoV. The average COVID-19 mortality was 2.3%, lower than the SARS-CoV and MERS-CoV mortality. The COVID-19 outbreak was also thought to have started from a local seafood sales market in winter, an environment that was almost the same as the SARS virus outbreak. This scientific article will discuss in depth the operational definitions that can be used in the management of patients with suspected COVID-19 infection. It will also discuss clinical manifestations and management in patients with suspected and confirmed COVID-19 infection.